Singularities of the University Spin-off in Northern Argentina - Zachman, Patricia; Redchuk, Andrés (My University, 2016)
In recent decades, Argentinian universities, are inserted into the productive environment from creating business incubators university, turned into one of the mechanisms for technology transfer reference. These companies, known as Spin-Off, ideally arise from the knowledge generated within universities. This paper presents a brief summary, the findings of a study of the main characteristics and current status, degree of technological linkage of Argentinian universities geographically located in the north, to the conversion of scientific research in business and commercial value. The information was obtained through semi-structured interviews with a representative sample of spin-off members of accredited at the Ministry of Industry of the Nation and of secondary sources for the analysis of the factors affecting the growth of these companies’ interviews. The creation of companies born in the university is a complex phenomenon to study multifactorial reasons for intervening in it. This exploratory study can give some guidance to universities not copy a system, but that adapt best practices to their regional needs, academic infrastructure and economic investments and to obtain optimal results in the creation of technology-based companies.
Keywords: R+D+I; Spin off